Hambatan Komunikasi Antara Siswa dan Guru Di Lingkungan Sekolah MTS Al-Azhar Sei Siarti Kecamatan Panai Tengah Kabupaten Labuhanbatu - Eli Dawana (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Communication is the most important but also complex aspect of human life. Humans are greatly influenced by the communication they do with other humans, both those they already know and those they don't know at all. The problem encountered at MTs Al-Azhar Sei Siarti is that there are still many communication barriers that occur within the school environment. This can be seen based on the observations that the researchers made which illustrated that many students were shy about expressing opinions, students hesitated in starting a conversation, felt uncomfortable when asking for help from friends or teachers to clarify subjects that were not understood, always being alone, not wanting to join with other friends and many more problems that arise in the MTs Al-Azhar Sei Siarti school environment. Communication barriers are very interesting to study because of the importance of communication between students and teachers so that learning that takes place can be more accepted by all students because there is no longer a sense of passivity between students and teachers. The purpose of this research is to find out what communication barriers occur between students and teachers at MTs Al-Azhar Sei Siarti school. In this study the authors used descriptive qualitative methods, namely analyzing by describing the subject and research object based on the phenomena that occur in the field. While the data collection techniques using interviews, observation, documentation, and data analysis techniques.The conclusion in this study is that there are communication barriers between students and teachers in the aspects of mechanical barriers, semantic barriers and ecological barriers.